ANALYSIS OF ASSESSMENT OF NOISE POLLUTION IN INDUSTRIAL ENTERPRISES (Intent Research Scientific Journal, 2024)
This paper presents an analysis of the assessment of noise pollution in industrial enterprises. Noise pollution in industrial settings is a significant occupational hazard that can have detrimental effects on the health and wellbeing of workers. This paper explores various methods of assessing noise pollution in industrial environments, including sound level measurements, noise mapping, and exposure assessments. The impact of noise pollution on workers' health and productivity is a crucial concern in industrial enterprises, and effective assessment methods are essential for monitoring and mitigating its effects. Additionally, compliance with regulatory standards for noise exposure is a legal requirement for industrial enterprises.